2014
DOI: 10.1063/1.4885378
|View full text |Cite
|
Sign up to set email alerts
|

Octupolar out-of-plane magnetic field structure generation during collisionless magnetic reconnection in a stressed X-point collapse

Abstract: The out-of-plane magnetic field, generated by fast magnetic reconnection, during collisionless, stressed X-point collapse, was studied with a kinetic, 2.5D, fully electromagnetic, relativistic particle-in-cell numerical code, using both closed (flux conserving) and open boundary conditions on a square grid. It was discovered that the well known quadrupolar structure in the out-of-plane magnetic field gains four additional regions of opposite magnetic polarity, emerging near the corners of the simulation box, m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Following Graf von der Pahlen & Tsiklauri (2014a), Graf von der Pahlen & Tsiklauri (2014b), and Graf von der Pahlen & Tsiklauri (2015), this study continues the investigation of X-point collapse using a relativistic and fully electromagnetic PIC code. While in previous studies the simulation runs were limited to 2.5D, in this study results were extended into 3D.…”
Section: Pic Simulation Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Graf von der Pahlen & Tsiklauri (2014a), Graf von der Pahlen & Tsiklauri (2014b), and Graf von der Pahlen & Tsiklauri (2015), this study continues the investigation of X-point collapse using a relativistic and fully electromagnetic PIC code. While in previous studies the simulation runs were limited to 2.5D, in this study results were extended into 3D.…”
Section: Pic Simulation Set-upmentioning
confidence: 99%
“…the formation of a current sheet, magnetic Hall field generation, and independence of system size. However, simulations of X-point collapse have also uncovered several new features, such as initial oscillatory reconnection and vortex formation in the high guide-field regime (Graf von der Pahlen & Tsiklauri 2014a) and a distinct octupolar out-of-plane magnetic field (Graf von der Pahlen & Tsiklauri 2014b, which makes this set-up a useful device for the ongoing study of magnetic reconnection. In this study we extend the results of Graf von der Pahlen & Tsiklauri (2014a) where collisionless X-point collapse with a magnetic guide-field was investigated in a 2.5 PIC simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The out-ofplane magnetic field that emerged in Ref. [16] was shown to have the well-known quadrupolar field at the centre, generated by electron currents, and four regions of opposite magnetic polarity on the outside, resulting from ion currents, as illustrated in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…(Right panel) The setup and resulting current and out-ofplane magnetic field generation for X-point collapse, from simulations in Ref. [16]. It is shown that, as in-plane field lines reconnect, electrons move towards and then away from the X-point, generating quadrupolar structure as described in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation